Расчёт температурных полей в составном полубесконечном теле с учётом обобщённого закона Фурье - Ячменёв, Владимир Александрович; Николенко, Валентина Владимировна (НТУ "ХПИ", 2016)
Рассматривается задача расчёта температурных полей в составном полубесконечном теле. В качестве модели принято уравнение теплопроводности с дробной производной, которая учитывает нелокальность тепловых процессов по времени. На границе полосы и полупространства предполагается идеальный тепловой контакт. Задача решена с помощью преобразования Лапласа. На основании тауберовых теорем получено асимтотическое решение для малых времён. Решение записано в виде обобщённых рядов.

Temperature fields in extended solids and the solids that have symmetry can be described with a high degree of accuracy by one-dimensional heat conduction equation. In this scientific paper the half-space with the layer is simulated using one-dimensional compound bar and consideration is given to the problem of calculation of temperature fields in the compound semi-infinite bar the finite and semi-infinite parts of which have different thermal physical parameters. The heat conduction equation with the fractional derivative in time that takes into account the nonlocality of thermal processes in time is taken as a mathematical model.
Calculation of temperature fields in a composite semi-infinite body taking Into account the generalized fourier law
Keywords: уравнение теплопроводности; дробная производная; идеальный тепловой контакт; функции Маинарди; heat conduction equation; fractional derivative; ideal thermal contact; Mainardi function